2019
DOI: 10.1111/ecc.13166
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of psychological distress in breast cancer survivors: A biopsychosocial approach

Abstract: Objective A cross‐sectional study was conducted to examine the extent to which perceived social support, cortisol‐awaking response (CAR) and tumour necrosis factor alpha (TNF‐α) interact to statistically predict psychological distress in breast cancer survivors. Method Moderation analyses were performed to study the influence of some psychobiological variables on psychological distress. The sample was comprised by 80 survivor women. Results TNF‐α moderate the relation between social support and psychological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 60 publications
2
16
1
1
Order By: Relevance
“…According to Rosemberg et al (2017), the goal of this framework is not only to prevent the onset of disease originating from overload, but also to leverage adaptation for optimal health under the circumstances. Aligning this principle with our findings, although being younger seems to increase the risk of suffering from distress, it has also been reported that young breast cancer survivors may, in turn, benefit more from social support, improving coping skills and expanding opportunities for information-sharing (Chou et al, 2012;Perez-Tejada et al, 2019). Monoamine and metabolite levels may also be interpreted as modifiable risk factors, and not only via 5-HT and noradrenaline reuptake inhibitors.…”
Section: Discussionsupporting
confidence: 86%
“…According to Rosemberg et al (2017), the goal of this framework is not only to prevent the onset of disease originating from overload, but also to leverage adaptation for optimal health under the circumstances. Aligning this principle with our findings, although being younger seems to increase the risk of suffering from distress, it has also been reported that young breast cancer survivors may, in turn, benefit more from social support, improving coping skills and expanding opportunities for information-sharing (Chou et al, 2012;Perez-Tejada et al, 2019). Monoamine and metabolite levels may also be interpreted as modifiable risk factors, and not only via 5-HT and noradrenaline reuptake inhibitors.…”
Section: Discussionsupporting
confidence: 86%
“…Ikerketa-lerro berean jaso ditugun beste datu batzuen arabera, bularreko minbizia gainditutako emakumeengan, TNF-α maila altuak eta babes sozial eskasa aldi berean ematen direnean, distres psikologikoa handiagoa da (26). Emaitza horiek, lan honetan aurkeztutakoekin batera, zera adierazten dute: TNF-α eta kortisol-maila altuak nahasmendu afektiboak izateko arrisku handiagoarekin lotzen badira ere, babes sozialak eta erronkari aurre egiteko baliabideak izateak antsietate-edo depresio-sintomen agerpena modula dezaketela.…”
Section: Etorkizunerako Planteatzen Den Norabideaunclassified
“…In fact, the American College of Surgeons Commission on Cancer now requires documentation of distress as part of Comprehensive Cancer Center accreditation 3 . Previous literature suggests that cancer patients manifest measurable physiologic stress as well, 4,5 and the relationship between physiologic stress and patient‐reported distress is an active area of research 6‐8 …”
Section: Introductionmentioning
confidence: 99%
“…3 Previous literature suggests that cancer patients manifest measurable physiologic stress as well, 4,5 and the relationship between physiologic stress and patient-reported distress is an active area of research. [6][7][8] Causal mechanisms to explain the associations between patient-reported distress, physiologic stress, and clinical outcomes are incomplete, however, and require further study to provide a framework to improve patient care. Identification of patient characteristics associated with or even predictive of high levels of distress could clarify the nature of distress in cancer patients and guide development of appropriate interventions to minimize distress-related adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%